SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENYALURAN BERAS BERSUBSIDI MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Abdussalam Al Akbar; Sapri Sapri; Leni Natalia Zulita (Jurnal Media Infotama, 2014)
Subsidized rice is one government program to help people who are not capable of in terms of food, in order to reduce mortality and malnutrition affected due to difficult taking one of the main food staple of man. Thus it is necessary decision support system assisting the government to give the decision to the person entitled to receive the subsidized rice. The research was done at Kelurahan Jalan Gedang yang terdapat di Kecamatan Gading Cempaka, Provinsi Bengkulu. In con-ducting this research, the writer used the System Development Life Cycle (SDLC). Steps in designing a system that includes analysis of the system in general and in detail using the tools of Data Flow Diagrams (DFD) and Entity Relation Diagram (ERD). The development of this system is carried out using Visual Basic 6.0. The results showed that the exist-ence of this program can be used as aids in the manufacture of valid data about the reception Raskin, so as to facilitate the completion of the work. The existence of this system can also make the management and performance become more effective and efficient.Keywords: Decision Support Systems, Location Marketing, MySQL, Visual Basic 6.0